Pengaruh Pemberian Garam (NaCl) terhadap Kerusakan Telur Argulus Japonicus [Effect of Salt (NaCl) Against Damage of Argulus japonicus Egg] - Kismiyati Kismiyati; Rakhmarani Nur Fatiza; Rahayu Kusdarwati (Faculty of Fisheries and Marine Universitas Airlangga, 2011)
Abstract A. japonicus is a freshwater parasite which belonging as obligate parasite. Prevention and control of A. japonicus attacks still used an insecticides, such as organophosphates and other chemicals which are used as a control. The chemicals can damage environment and around the ecosystems. Salt (NaCl) can be used as control of A. japonicus infestation. NaCl is often used as A. japonicus control. The residues effect of using NaCl in fish culture is not known clearly. Therefore, NaCl can still be known as safety chemicals for aquaculture activities. This study aimed to inhibit hatching rate of A. japonicus. Definition the damage of egg is difference the egg condition from early condition and not whole return. In addition to, the damage process is refer to osmose dehydration. The study method was done by experiment with the experimental design was used Completely Randomized Design (CRD) with six treatments and five replicates. NaCl which used are 60 g/l, 70 g/l, 80 g/l, 90 g/l, 100 g/l and control. The main parameter is the percentage of hatching rate of A. japonicus. The support parameter on the research are otemperature (C), pH, DO (mg/l). Data analysis is using Analysis of Variance (ANOVA). The results showed that dipping with NaCl the influence of damage of A. japonicus eggs, but the analysis statistic did not provide the real difference treatment.